Palm Sugar Product Processing Diversification - Zainuddin Rahman; Syamsu Nujum (Advances in Community Services Research, 2023)
The Palm Sugar Craftsmen Group in Borisallo Village is one of the sugar producing groups in Tinggi Mocong District, Gowa Regency with 20 members. The potential for palm sugar raw material sourced from sap water is quite large to be developed in the future, considering that this area has very adequate palm tree potential. ends in October 2020. The method used in PKM activities is a method of training and mentoring partners related to production, branding, packaging, and marketing processes to change the group production process from traditional methods to more advanced by implementing innovations in sugar in the form of liquid sugar ant sugar and sugar molding with a new method. Through service activities, the community can help partners to facilitate through entrepreneurial guidance and training, so that they can produce sugar variants through product diversification, packaging and branding so as to increase added value and increase group income